The Effect of Adding Electrolytes (NaCl) in Tunjung Mordan on Ecoprint Results Using Jatropha curcas Linn Leaves with Pounding Technique on Chiffon Material - Mitra Ramadhani; Adriani Adriani (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
This research is motivated by the use of jatropha leaves to make motifs with the ecoprint technique. The purpose of this study is to describe the color name, color fastness and the effect of adding electrolyte to the tunjung mordan on the results of ecoprint by pounding technique on chiffon material. The type of research is experimental research with primary data types sourced from filling out a questionnaire of 18 panelists. Ecoprint of jatropha leaves without mordan produces the names of canary yellow on leaf sheets, pale golden on leaf bones, and reef green leaf bone branches. With mordan tunjung produces dark olive green on the leaf sheet, canary yellow on the leaf bone mother, and reef green on the leaf bone branch. The addition of electrolytes to the tunjung mordan produced the name of camouflage green on the leaf leaf, green smoke on the leaf bone, and reef green on the leaf bone branch. The color fading resistance to washing in chiffon material without mordan, in mordan tunjung, and the addition of electrolyte to mordan tunjung 1time and 2times Ho washing was declared accepted, meaning that there was no significant difference in the results of the K-Related Sample test on color fastness to washing. While 3times of washing Ho was rejected, it means that there is a significant difference in the results of the K-Related Sample test on color fastness to washing.